Maximal lactate steady state in kayaking - Li, Y.; Niessen, M.; Chen, X.; Hartmann, U. (International Journal of Sports Medicine, 2014)
A fixed blood lactate value of 4 mM was commonly used to calculate workload at maximal lactate steady state (MLSS) in kayaking. Our purpose was to measure the actual blood lactate value at MLSS and workload at MLSS in kayaking and assess the validity of using a fixed blood lactate value to calculate the workload at MLSS. 8 junior kayakers (15.1±1.2 years; 179.9±7.3 cm; 72.3±4.9 kg) participated in an incremental workload test and 4-6 sub-maximal constant workload tests (duration of 30 min) on a kayaking ergometer. Blood lactate was measured to calculate the blood lactate value and workload at MLSS. The blood lactate value at MLSS in kayaking was 5.4±0.7 mM. The measured workload at MLSS (112±22 watts) was significantly greater than the calculated workload using a lactate value of 4 mM (104±18 watts, p=0.016). The measured MLSS workload was not significantly different from the calculated workload using a fixed lactate value of 5.4 mM (115±19 watts, p=0.16) or 5.0 mM (113±19 watts, p=0.78) in the incremental tests. A fixed blood lactate value of 5 mM instead of 4 mM might be a better estimate in kayaking given the incremental workload test used in this study.